Effect of three rates of nitrogen, phosphorus and potassium over passion fruit production - Faria, João L. C.; Colauto, Neusa M.; Manica, Ivo; Stronski, Maria dos S.; Appel, Henrique B. (Pesquisa Agropecuária Brasileira, 1991)
The objective of this work was to evaluate the effect of three rates of nitrogen, phosphorus and potassium over passionfruit production. The experiment was conducted in Guaíba county in Rio Grande do Sul, Brazil, on a São Jerônimo Soil (ULTISOL). The annual average yield ranged from 13.7 to 16.7 tons/ha according to treatments. The statistical analysis did not show any difference due to the treatments. The leaf macro nutrients content was adequate to the crop.